PENDIDIKAN KARAKTER DI KELUARGA - Ahmad Zainuri (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2018)
Family is the first and foremost environment for a human child. In the family a child is raised, learns the ways of association that he will develop later in the social life environment that is outside the family. In simple terms it can be argued that the function of the family is to stabilize the family situation in the sense of stabilizing the family's economic situation. Then the family functions also educate and maintain the physical and psychological family, including religious life. Here the role of parents, especially mothers, is very influential on the development of the child. Family education is called primary education because in this environment all human potential is formed and partially developed. There are even some potentials that have developed in family education. Children will grow up to be characterless individuals if they can grow in a characteristic environment, so that the nature of every child born holy can develop optimally. Character education must start from the family to build a noble national personality. To achieve the child's character expected by parents, parenting given by the family to children is closely related to the character of the child in his growth and development. These characters will be carried to adulthood even if they form their own family. On the contrary, family failure in shaping children's character will result in the growth of a society that has no character. Therefore, every family must have an awareness that the formation of children's character is very dependent on character education at home. Furthermore, Megawangi (2003) mentions that there are at least three basic children's needs that must be met, namely maternal bonding, security, and physical and mental stimulation